MECHANISMS FOR ACHIEVING A BALANCE BETWEEN FISCAL EFFICIENCY AND SOCIAL JUSTICE IN THE SYSTEM OF PUBLIC TAXATION MANAGEMENT - Kulibaba, Yevgenii (Public Management and Policy, 2026)
The article examines key tax policy and administration tools that allow balancing fiscal efficiency with social justice. Tax policy involves a balance between ensuring the necessary state revenues and promoting inclusive growth. At the same time, tax equity means adhering to the principles of progressivity, horizontal and vertical equity. An analysis of theoretical sources shows that the taxation system is the main mechanism for redistributing income, but there is a potential trade-off between efficiency and equity. Increasing the tax base and simplifying administration usually increase revenues (efficiency), while progressive rates and targeted benefits strengthen social justice, although they can complicate the system and restrain economic incentives. The article analyzes conceptual mechanisms and general world experience, but does not provide detailed empirical modeling of a single country. Therefore, the recommendations are of a generalized nature. Relevant sources for 2015–2025 are taken into account, but despite this, some specific recent changes (for example, updates to individual national codes 2025–2026) may not be taken into account. In addition, a combination of political factors (electoral cycles) and legal features of individual countries may change the real acceptability of the proposed measures. For example, high progressivity may be ideal in countries with a strong tradition of redistribution, but it will not work where opposition from business or politicians unwilling to raise rates is expected. These nuances may be the subject of further research. Also, modern theoretical approaches and empirical evidence on the impact of tax instruments on fiscal efficiency and redistribution are summarized. A comparative analysis of tax mechanisms and practices in six countries with different models (Scandinavia, continental Europe, the Anglo-Saxon model, transition economies, and countries with high evasion) is conducted. It is noted that Scandinavian countries, such as Denmark, achieve a very high tax burden (≈45% of GDP) due to a broad VAT base and significant revenues from personal income tax; in contrast, in the USA, the tax system, in particular due to the absence of VAT, yields significantly lower revenues (≈26% of GDP), mostly due to the household income tax and local property taxes. In Germany and Poland, social contributions account for a large share of the revenue structure (over 35%), which reflects the continental model of the welfare state. At the same time, in countries with a high level of evasion (generally in Latin America and the Caribbean), losses from the shadow economy reach ≈6.3% of GDP. According to the results of the analysis, for practitioners with limited resources, it is recommended: 1) to focus on expanding the tax base (fighting evasion, formalizing small businesses) and simplifying administrative procedures; 2) gradually introduce progressivity (charge higher rates on higher incomes) and flexible benefits for vulnerable groups, minimizing deficits (rounding rates, efficiency/inclusiveness trade-offs); 3) use digital technologies (e-declaration, automated data, e-invoices) to increase transparency and ensure adequate revenues. The article provides clear recommendations adapted to the conditions of resource-constrained states, and also analyzes possible compromises and priorities.